Nontuberculous mycobacterial pulmonary disease: an integrated approach beyond antibiotics. Issue 2 (24th May 2021) - Faverio, Paola; De Giacomi, Federica; Bodini, Bruno Dino; Stainer, Anna; Fumagalli, Alessia; Bini, Francesco; Luppi, Fabrizio; Aliberti, Stefano
Nontuberculous mycobacterial (NTM) pulmonary disease (PD) is an emerging condition with heterogeneous manifestations from both the microbiological and the clinical point of view. Diagnostic and therapeutic guidelines are available but there are still unmet patients' and physicians' needs, including therapy-related adverse events, symptom control, management of comorbidities, risk of re-exposure to the pathogen and unfavourable outcomes. In the present review, we provide currently available evidence for an integrated approach to NTM-PD beyond antibiotic therapy. This includes 1) avoiding exposure to environments where mycobacteria are present and careful evaluation of lifestyle and habits; 2) implementing a personalised pulmonary rehabilitation plan and airway clearance techniques to improve symptoms, exercise capacity, health-related quality of life (QoL) and functional capacity in daily living activities; 3) a nutritional evaluation and intervention to improve health-related QoL and to control gastrointestinal side-effects during antimicrobial therapy, particularly in those with low body mass index and history of weight loss; and 4) managing comorbidities that affect disease outcomes, including structural lung diseases, immune status evaluation and psychological support when appropriate. An integrated approach, including risk factor prevention, management of comorbidities, nutritional evaluation and intervention and pulmonary rehabilitation, should be considered in the optimal management of nontuberculous mycobacterial pulmonary disease https://bit.ly/2YEqvQg